Sammy Keyes and the psycho Kitty Queen - Van Draanen, Wendelin (Van Draanen, Wendelin. Sammy Keyes mysteries., 2006)
When cats begin to mysteriously disappear in Santa Martina, thirteen-year-old friends Sammy and Holly start snooping around town to find out what is happening.